CHARACTERISTICS OF THE BODY SIZE OF THE SENDURO GOAT WHICH IS ORIGIN FROM SENDURO, LUMAJANG, EAST JAVA - Prasetyo, Guruh; Susilorini, Tri Eko; Septian, Wike Andre; Tribudi, Yuli Arif; Efendi, Ahmad Zarkasi; Hidayah, Nur; Damayanti, Heri; Suyadi, Suyadi (Jurnal Veteriner; Vol 24 No 2 (2023)DO - 10.19087/jveteriner.2023.24.2.230, 2023)
Germplasm diversity is a valuable source of genetic material whose existence needs to be protected and preserved. One of the original Indonesian goat germplasms is Senduro goat, which has been established by the Decree of the Ministry of Agriculture Republic of Indonesia No. 1055/Kpts/ SR.120/10/2014 and originates from Senduro District, Lumajang Regency, East Java. The purpose of the study was to analyze the phenotypic traits of Senduro goats based on their quantitative traits. Phenotype observations include body length, chest circumference, shoulder height, ear length, and rewos hair length and correlate each phenotype trait. The materials used in this study were 14 and 25 head of adult male and female Senduro goats, respectively. Senduro goats that were observed in the condition of incisor the thirdth (I3 ) were replaced by permanent teeth, it mean the Senduro goats aged 2-4 years. The morphometric data obtained were calculated as mean, standard deviation, and correlation between morphometric measures using the Genstat 14.2 program and then analyzed descriptively. The results of this study showed that Senduro goats had a body weight of 24.56 ± 5.48 kg (male) and 26.84 ± 6.50 kg (female), a body length of 63.89 ± 4.76 cm (male) and 63.32 ± 6.29 cm (female), a chest circumference of 61.67 ± 4.36 kg (male) and 66, 48 ± 6.56 cm (female), a shoulder height of 66.33 ± 4.53 cm (male) and 64.71 ± 5.76 cm (female), ear length of 31.22 ± 2.17 cm (male) and 28.13 ± 2.74 cm (female), and length of rewos/surai hair of 17.56 ± 1.67 cm (male) and 14.58 ± 2.39 cm (female) Morphometric measures in Senduro goats are positively correlated with each other. There is a highly significant correlation between chest circumference, body length, and height and body weight in Senduro goats.